Bank Islam Brunei Darussalam (BIBD) as a Pillar of National Sharia Finance: A Study of Its Historical Development, Operational Framework, and Role in the Global Financial System - Gama Pratama (Ecobankers : Journal of Economy and Banking, 2026)
This study examines the strategic role of Bank Islam Brunei Darussalam (BIBD) as the central pillar of Islamic finance in Brunei Darussalam. The country’s financial system is strongly supported by BIBD as its leading Islamic banking institution. The research aims to analyze BIBD’s historical development, operational management, Islamic banking products, and its contribution to both the national economy and the global financial system. This study employs a qualitative descriptive approach, utilizing secondary data from academic literature, institutional reports, and official publications related to BIBD. The findings reveal that BIBD possesses a strong institutional foundation, supported by integrated governance and strict adherence to Sharia principles. Its banking products emphasize fairness, transparency, and risk-sharing, which contribute to maintaining public trust. Despite its dominance in the domestic market, BIBD faces several global challenges, including increasing international competition, rapid digital transformation, and the need for harmonization of Sharia standards across jurisdictions